2003
DOI: 10.1002/prot.10539
|View full text |Cite
|
Sign up to set email alerts
|

Predicting interresidue contacts using templates and pathways

Abstract: We present a novel method, HMMSTR-CM, for protein contact map predictions. Contact potentials were calculated by using HMMSTR, a hidden Markov model for local sequence structure correlations. Targets were aligned against protein templates using a Bayesian method, and contact maps were generated by using these alignments. Contact potentials then were used to evaluate these templates. An ab initio method based on the target contact potentials using a rule-based strategy to model the protein-folding pathway was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(42 citation statements)
references
References 29 publications
0
42
0
Order By: Relevance
“…It has successfully been used to predict protein three-dimensional local structures, secondary structures, to identify protein-coding ORFs, or to design a sequence to fit a structure. Recently, a two-dimensional approach has been developed with HMMSTR-CM [384]. The latter predicts the likelihood of pairwise inter-residue contacts.…”
Section: D-blastmentioning
confidence: 99%
“…It has successfully been used to predict protein three-dimensional local structures, secondary structures, to identify protein-coding ORFs, or to design a sequence to fit a structure. Recently, a two-dimensional approach has been developed with HMMSTR-CM [384]. The latter predicts the likelihood of pairwise inter-residue contacts.…”
Section: D-blastmentioning
confidence: 99%
“…Numerous sequence-based methods have been developed using machine learning algorithms such as artificial neural networks (ANNs) (Fariselli and Casadio, 1999;Fariselli et al, 2001;Pollastri et al, 2001;Punta and Rost, 2005;Tegge et al, 2009;Vullo et al, 2006;Xue et al, 2009;Zhang and Huang, 2004), support vector machines (SVMs) (Cheng and Baldi, 2007;Wu and Zhang, 2008;Zhao and Karypis, 2005), Hidden Markov Models (HMM) (Bjorkholm et al, 2009;Shao and Bystroff, 2003), Genetic Algorithm (GA) (Chen and Li, 2010;MacCallum, 2004), etc. The mean accuracy achieved by state-of-the-art RR predictors is often in the range of 20-30%, suggesting that it remains in need of improvement.…”
Section: Introductionmentioning
confidence: 99%
“…Construction of residue contact maps for protein structures and statistical evaluation of residue colocations is a frequently used method for visualization and analyses of spatial connections between amino acids [27][28][29]. The amino acid co-locations in real protein structures is clearly not random [30,31] and therefore residue co-location matrices are often used to assist in the prediction of novel protein structures [32,33]. We have carefully examined the physicochemical properties of specifically interacting amino acids in and between protein structures, and we concluded that these interactions follows the well known physico-chemical rules of size, charge and hydrophobe compatibility (unpublished data) well in line with Anfinsen's prediction.…”
Section: Resultsmentioning
confidence: 99%